2007
DOI: 10.1063/1.2757146
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoelectric effect (under a dc magnetic bias of 2Oe) in laminate composites of FeBSiC alloy ribbons and Pb(Zn1∕3,Nb2∕3)O3–7%PbTiO3 fibers

Abstract: Giant magnetoelectric (ME) voltage and charge coefficients have been found in long-type composites of high-permeability magnetostrictive FeBSiC alloy ribbons laminated together with piezoelectric Pb(Zn1∕3,Nb2∕3)O3–7%PbTiO3 single crystal fibers. The maximum ME voltage and charge coefficients at low frequencies were 10.5V∕cmOe and 1nC∕Oe under a notably low dc magnetic bias of 2Oe; at resonance, these coefficients were dramatically increased to 400V∕cmOe and 42nC∕Oe, respectively. These values are much higher, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…ceramic-ceramic particle composites of two phases, and Terfenol-D/piezoelectric ceramic particles/polymer three phases) and 2-2 (magnetostrictive/piezoelectric) laminates [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . These studies confirmed the existence of ME effects in single phase materials or multi-phase composites; and amongst them, giant ME coupling has been found in magnetostrictive/piezoelectric two-phase 2-2 laminate composites, and in recent 2-1 laminates [33,34] .…”
Section: Magnetoelectric Equivalent Circuit Analytical Methods Is Pressupporting
confidence: 70%
“…ceramic-ceramic particle composites of two phases, and Terfenol-D/piezoelectric ceramic particles/polymer three phases) and 2-2 (magnetostrictive/piezoelectric) laminates [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . These studies confirmed the existence of ME effects in single phase materials or multi-phase composites; and amongst them, giant ME coupling has been found in magnetostrictive/piezoelectric two-phase 2-2 laminate composites, and in recent 2-1 laminates [33,34] .…”
Section: Magnetoelectric Equivalent Circuit Analytical Methods Is Pressupporting
confidence: 70%
“…Thus, researchers commonly select large samples for their low electromechanical resonance frequency. 5,[7][8][9][10] This is unfavorable to miniaturize devices. Whereas, dynamic electric field with high frequency is easily applied on the sample for Z c =1/ C p during EIM measurement, where C p is the capacitance of the sample.…”
Section: Giant Electric-field-induced Magnetization In a Magnetoelectmentioning
confidence: 98%
“…14 On the other hand, the MIE measurement commonly requires Helmholtz coils to generate a dynamic magnetic field. [8][9][10] The impedance of the Helmholtz coils is Z L = L s , where L s is the inductance of the coils, resulting in a difficulty to obtain high-frequency magnetic field. Thus, researchers commonly select large samples for their low electromechanical resonance frequency.…”
Section: Giant Electric-field-induced Magnetization In a Magnetoelectmentioning
confidence: 99%
“…The high piezoelectric response and the low dielectric constant, due to the strong texturing of the PZT grains and their domain state, presumably contributed to the larger ME output, since α ME ∝ g ij (=d ij /ε ij ), where ε ij is dielectric permittivity and g ij and d ij are piezoelectric voltage and charge coefficients, respectively. 31,32 The low permittivity achieved in predominantly c-domain films is useful in increasing the α ME value. It is also believed that the reduced substrate clamping in the PZT film due to the film on the foil structure and the strong interfacial bonding of the PZT/LNO/HfO 2 /Ni heterostructure should allow for better strain transfer and in turn stronger ME coupling between PZT and Ni.…”
mentioning
confidence: 99%